Biliary excretion of ciprofloxacin and piperacillin in the obstructed biliary tract. - van den Hazel, S J (1996)
Biliary excretion of ciprofloxacin and piperacillin was determined in cholestatic patients who had undergone endoscopic cholangiography. The median concentration of ciprofloxacin (n = 9) was 2.36 micrograms/ml (range, 0.29 to 19.8 micrograms/ml) in bile compared with 1.66 micrograms/ml (range, 0.73 to 2.69 micrograms/ml) in serum. The median concentration of piperacillin (n = 7) was < 5 micrograms/ml (range, < 5 to 26) in bile compared with 14.3 micrograms/ml (range, 5.3 to 80) in serum. Ciprofloxacin, but not piperacillin, can be actively excreted into bile in the presence of a biliary tract obstruction.